Nosocomial infections and antibiotic resistance in a tertiary university hospital pediatric intensive care unit (Annals of Medical Research, 2021)
Aim: Nosocomial infections (NI) cause failed treatments and long hospitalization periods in pediatric intensive care units (PICUs), leading to severe rates of mortality, morbidity and high hospitalization costs. This study intends to offer a retrospective review of the types of NI, active pathogens as well as antibiotic resistance profiles of inpatients followed up and treated in the PICU of a tertiary university hospital.Material and Methods: In this study, in-patients who were treated in an intensive care unit between January 2014 and June 2018 were evaluated retrospectively. Patients’ data were obtained from the Infection Control Committee database. Based on this data, the rate of NIs, the distribution of NIs by the systems, the invasive device-related infection rate, the infectious agents and the antibiotic resistance of these agents at the PICU were determined within the specified time-frame.Results: In this study, 536 patients receiving treatment at a PICU between January 2014 and June 2018 were examined. A NI episode developed in 69 (12.6%) of these patients. The NI rate was 12.87/100 applications. The mean hospitalization length of stay of the patients was 17.65 days. Bloodstream infections due to the use of central venous catheters were the most common form of NI. In this study, of all the NI agents, Gram (-) microorganisms were isolated the most. The most commonly isolated microorganism was Acinetobacter baumannii (A. baumannii). The rate of carbapenem resistant A. baumannii was 85%.Conclusion: In PICUs, surveillance measures for infection control and rational use of antibiotics are important in terms of preventing high mortality and morbidity rates and hospitalization costs due to resistant microorganisms.Keywords: Nosocomial infection; bloodstream infections; pediatric Intensive care unit.